Bibliometric Analysis of Scopus Database in Mapping Green Economy Business Research - Rio Saputra Simanjuntak; Hendro Sutomo Ginting; Jordan Putra Cahyono (Information Technology and Science (ITScience), 2026)
The green economy has emerged as a crucial idea for advancing sustainable development and tackling environmental concerns. The rising interest in sustainable business practices has resulted in a substantial surge in research on the green economy. Nevertheless, the current literature is fragmented across various fields, necessitating a thorough synthesis of research advancements in this area. This study intends to identify the research landscape of green economy business by a bibliometric analysis of publications included in the Scopus database. Three hundred fifty-seven publications published from 2008 to 2024 were analysed employing descriptive bibliometric approaches and visualised using VOSviewer software. The analysis concentrated on publication patterns, prominent journals, prolific authors, institutional connections, countries, citation performance, and research areas. The data indicate significant growth in publications, especially post-2020, reflecting heightened academic interest in green economy industry. China was recognised as the most productive nation, succeeded by the United Kingdom and the United States. The most significant research mostly concentrate on circular economy business models, sustainable production, and waste management. Keyword analysis indicated that green entrepreneurship, business models, development, and green investment are the predominant research themes. This study elucidates the progression of green economy business research and furnishes valuable insights for researchers, practitioners, and policymakers to facilitate the transition to a more sustainable and ecologically responsible economy.